2019
DOI: 10.1002/pmic.201700453
|View full text |Cite
|
Sign up to set email alerts
|

Surfaceome of Exosomes Secreted from the Colorectal Cancer Cell Line SW480: Peripheral and Integral Membrane Proteins Analyzed by Proteolysis and TX114

Abstract: Exosomes are important bidirectional cell–cell communicators in normal and pathological physiology. Although exosomal surface membrane proteins (surfaceome) enable target cell recognition and are an attractive source of disease marker, they are poorly understood. Here, a comprehensive surfaceome analysis of exosomes secreted by the colorectal cancer cell line SW480 is described. Sodium carbonate extraction/Triton X‐114 phase separation and mild proteolysis (proteinase K, PK) of intact exosomes is used in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 88 publications
(134 reference statements)
2
42
1
1
Order By: Relevance
“…A role in the modulation of autophagy was also revealed for the heterogeneous nuclear ribonucleoprotein K (HNRNPK) and M (HNRNPM) [61,64]. Further ribosomal proteins-namely RPL5, RPL6, RPL12, RPL18, RPL22, RPS16, and RPS4X-were identified, possibly due to their RNA-binding property or, as recently reported, being present on the surface of exosomes [65].…”
Section: The Gabarap Co-secretome As Defined By Proximity Labellingsupporting
confidence: 55%
“…A role in the modulation of autophagy was also revealed for the heterogeneous nuclear ribonucleoprotein K (HNRNPK) and M (HNRNPM) [61,64]. Further ribosomal proteins-namely RPL5, RPL6, RPL12, RPL18, RPL22, RPS16, and RPS4X-were identified, possibly due to their RNA-binding property or, as recently reported, being present on the surface of exosomes [65].…”
Section: The Gabarap Co-secretome As Defined By Proximity Labellingsupporting
confidence: 55%
“…29 EVs may act as signaling complexes by direct stimulation of target cells, by transferring surface receptors between cells, and by delivering proteins, mRNA and bioactive lipids into the target cells. Recently, the surfaceome of EVs has been characterized, which has provided insights into the tropism capacity of EVs, 30 such as through various exosomal integrins to mediate organ-specific delivery. 31 We have utilised global cell surface expression and cardiac subcellular membrane studies to correlate key proteins associated within EVs as potential molecular bias for cardiac tropism and cell surface interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that LGALS3BP plays a key role in the cross-talk between neuroblastoma cells and the tumor microenvironment (TME) [ 17 ]. Indeed, LGALS3BP is one of the most abundant surface component of cancer-derived EVs [ 18 , 19 , 20 ]. EVs have a prominent role in inducing a TME that is favorable to cancer progression through the induction of immune escape, stimulation of angiogenesis and preparation of the pre-metastatic niche [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%